Influence of exogenous hydrogen peroxide on plant physiology, leaf anatomy and Rubisco gene expression of the Ficus deltoidea Jack var. deltoidea - Jamaludin, Rosnah; Mat, Nashriyah; Mohd, Khamsah Suryati; Badaluddin, Noor Afiza; Mahmud, Khairil; Sajili, Mohammad Hailmi; Khandaker, Mohammad Moneruzzaman (MDPI, 2020)
This study was carried out to investigate the regulatory effects of hydrogen peroxide (H2O2) on the growth, photosynthesis, biochemical properties, leaf anatomy and Rubisco gene expression in Ficus deltoidea var. deltoidea, a slow-growing medicinal herb. Results showed that 20-mM H2O2 treatment increased plant height, net photosynthetic rate, stomatal conductance and chlorophyll content of the plants by 10%, 20%, 127% and 57%, respectively, than a control plant. In addition, 20 mM H2O2 treatment significantly increased the carotene, total phenolic, total flavonoid and total sugar content than the control plant. The applications of H2O2 did not produce any negative effects on the leaf area, chlorophyll fluorescence, quantum yield or antioxidant activity of F. deltoidea plants. In regard to leaf anatomy, it was observed that the applications of H2O2 at 15 mM significantly improved cellular structure, leaf veins and promoted cell proliferation. Treated leaves developed a palisade layer, thickened leaf surface, the widest stomatal openings and a well-developed vascular bundle when compared to the control plant. Employing reverse transcription polymerase chain reaction (RT-PCR), the study showed that the Rubisco gene was expressed at a higher level in 15 mM H2O2 treatments than in 20 mM H2O2 treatments. The results indicate that H2O2 increased the Rubisco expression ratio up to 16-fold when compared to the untreated plants. It was conclusive that spraying 15 mM and 20 mM H2O2 twice a week enhanced growth, photosynthesis, the stomatal aperture, improved leaf anatomy and helped to regulate the expression of the Rubisco gene.